Liquid Organic Fertilizer Waste Painage Skin on Tomato Growth and Production in Alluvial Soil - Eko Bahtiyar Ciptono; Yoshep Ramtalungi; Lukman Pragustavi (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to obtain a concentration of POC of pineapple skin waste that can provide the best growth and yield of tomatoes in alluvial soils. The research was carried out from December 1, 2, 2019 to March 05, 2020 at the location located on Jalan Silat Baru, untan komplek. Pontianak City. The study used the Complete Randomized Design (RAL) method with one factor, which consisted of 5 treatments with 5 tests and each test consisted of 4 sample plants. The treatment in question is k1 = 10% POC pineapple skin waste, k2 = 15% POC pineapple skin waste, k3= 20% POC pineapple skin waste, k4 = 25% POC pineapple skin waste, k5 = 30% POC pineapple skin waste. The variables observed in this study were plant height, root volume, dry weight of plants, Number of Fruits Per plant, Fruit Weight Per Plant, and Weight Per Fruit. Based on the results of the study, it can be concluded that the application of POC pineapple skin waste with a concentration of 15% and 20% shows good growth at plant height 1 and 2 weeks after planting. Based on the results of the study, it can be concluded that from the administration of PINEAPPLE SKIN WASTE POC, it is not found that the best concentration but an efficient concentration for tomato growth and yield is 10% POC of pineapple skin waste.